Comparison of biomarkers of endothelial dysfunction and microvascular endothelial function in patients with primary aldosteronism and essential hypertension. (March 2021) - Sang, Miaomiao; Fu, Yu; Wei, Chenmin; Yang, Jing; Qiu, Xueting; Ma, Jingqing; Qin, Chao; Wu, Feiyan; Zhou, Xueling; Yang, Tao; Sun, Min
Introduction: Studies have shown that primary aldosteronism (PA) has a higher risk of cardiovascular events than essential hypertension (EH). Endothelial dysfunction is an independent predictor of cardiovascular events. Whether PA and EH differ in the endothelial dysfunction is uncertain. Our study was designed to investigate the levels of biomarkers of endothelial dysfunction (Asymmetric dimethylarginine, ADMA; E-selectin, and Plasminogen activator inhibitor-1, PAI-1) and assess the microvascular endothelial function in patients with PA and EH, respectively. Methods: The biomarkers of endothelial dysfunction were measured by enzyme-linked immunosorbent assay (ELISA). Microvascular endothelial function was evaluated by Pulse amplitude tonometry (PAT). Results: Thirty-one subjects with EH and 36 subjects with PA including 22 with aldosterone-producing adenoma (APA) and 14 with idiopathic hyperaldosteronism (IHA) were enrolled in our study. The ADMA levels among the three groups were different (APA 47.83 (27.50, 87.74) ng/ml vs EH 25.08 (22.44, 39.79) ng/ml vs IHA 26.00 (22.23, 33.75) ng/ml; p = 0.04), however, when the APA group was compared with EH and IHA group, there was no statistical significance (47.83 (27.50, 87.74) ng/ml vs 25.08 (22.44, 39.79) ng/ml for EH, p = 0.11; 47.83 (27.50, 87.74) ng/ml vs IHA 26.00 (33.75) ng/ml, p = 0.07). The results of ADMA levels are presented as Median (p25, p75). Whereas, levels of PAI-1 and E-selectin, microvascular endothelial function were not significantly different between PA and EH subjects. Conclusions: Our study shows no significant differences between PA and EH in terms of biomarkers of endothelial dysfunction and microvascular endothelial function. The microvascular endothelial function of PA and EH patients is comparable.